سيناريو سوء النية بالالزام بتطبيق المعايير الدولية لإعداد التقارير المالية في الشركات المدرجة: The Scenario of Bad Faith by Obligating the Application of IFRS in the Listed Companies - عبدالله ابراهيم نزال; أحمد مخلوف (Journal of North African Economies, 2025)
The study aimed to investigate the scenario of bad faith by obligating the application of IFRS in listed companies to lost real value and transferring wealth to the legal personality ownership by giving management the authority to act. The study followed a descriptive inductive approach, depending on previous studies and comparison with the jurisprudence of Islamic financial transactions. The results showed that the adopting IFRS is to follow the aimed of international legal consistency based on traditional accounting theories to conseder a court evidence for financial rights and to achieve an international level for countries economic and credit competitive ratings because of the relationship between global financial services institutions and the drafters of the IFRS. Inspite of IFRS adopting is not solve crises. The importance of the scenario appears by explaining the impact of IFRS adopting to increase foreign investment negatively by exploiting gap of injustice and deception levels to get lquidit from financial markets with a high value before the information is available, beside gap of separation between management and owners to control the local companies by their managing. And there is losing of evidence to prove the real value in objection case.